The modeling of different scale hydrologic - Voskoboinick, Volodymyr A.; Voskoboinyk, Oleksandr A.; Cherniy, Dmytro I. (КНУБА, 2019)
The results of mathematical and physical modeling of global and local hydrological processes in the water area are presented. By the method of mathematical modeling revealed variability of large-scale circulatory flow and mass transfer in a water-restricted area with complex obstacles. In laboratory conditions, by experimental methods, in the hydrodynamic tray, on the channel and the laboratory stand, detected of local hydrodynamic processes and mass transfer around local obstacles - three-row fuel burner rafts. Mechanisms of formation of erosion and transfer of the soil near and within the single and group structures of the grillages located on the laundering sandy bottom of the channel are revealed
Моделювання різномасштабних гідрологічних процесів в акваторії
Keywords: razversk; vortex structure; erozed soil; ростверк; вихрова структура; розмив ґрунту; 551.46.09:519